Pengaruh Optimalisasi Layanan dan Efisiensi Operasional Terhadap Tingkat Kepuasan Pasien Rawat Jalan di Rumah Sakit Urip Sumoharjo Bandar Lampung - Risal Wintoko; Farida Yuliaty; Ayu Laili Rahmiyati (Jurnal Ners, 2026)
Outpatient services constitute a fundamental component of hospital healthcare delivery systems and play a critical role in shaping patients’ perceptions of service quality and satisfaction. Patient satisfaction is influenced not only by clinical outcomes but also by the extent to which hospitals optimize service delivery and operational efficiency. This study was conducted to analyze the impact of service optimization and operational efficiency on outpatient satisfaction at Urip Sumoharjo Hospital, Bandar Lampung, in 2025. A quantitative approach with an observational analytic design was employed. Data collection utilized structured questionnaires administered to purposively selected outpatients, with research instruments subjected to validity and reliability testing. Data analysis comprised both descriptive and inferential statistics, including multiple linear regression to assess the partial and simultaneous effects of the independent variables. The findings indicate that both service optimization and operational efficiency positively and significantly influence patient satisfaction. Collectively, these variables make a meaningful contribution to enhancing outpatient satisfaction. These results underscore the importance of managing service delivery and operational processes not only to support clinical care but also to directly shape patient perceptions and satisfaction, thereby strengthening hospital reputation and competitiveness. Hospitals are advised to pursue continuous improvement through service innovation, digitalization of systems, and optimal resource management.